2012
DOI: 10.1007/s10120-012-0214-x
|View full text |Cite
|
Sign up to set email alerts
|

Value of splenectomy in patients with Siewert type II adenocarcinoma of the esophagogastric junction

Abstract: Splenic hilar lymph node dissection may be omitted without decreasing curability in patients with Siewert type II AEG, although a prospective study is necessary for more conclusive results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…10 lymph node dissection in patients with advanced proximal gastric cancer and is associated with better survival outcomes. However, many negative studies on the performance of splenectomy have been published because of the high morbidity rate and low survival benefit [28,29] . In addition, a randomized controlled trial (JCOG0110) more recently revealed that spleen preservation was non-inferior to splenectomy in overall survival for patients with gastric cancer that does not invade the greater curvature [30] .…”
Section: Discussionmentioning
confidence: 99%
“…10 lymph node dissection in patients with advanced proximal gastric cancer and is associated with better survival outcomes. However, many negative studies on the performance of splenectomy have been published because of the high morbidity rate and low survival benefit [28,29] . In addition, a randomized controlled trial (JCOG0110) more recently revealed that spleen preservation was non-inferior to splenectomy in overall survival for patients with gastric cancer that does not invade the greater curvature [30] .…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the impact of splenectomy on surgical outcome, a recent randomised trial reported that it failed to improve survival in patients with proximal gastric cancer not invading the greater curvature (7). Moreover, another study reported that splenectomy with splenic hilar lymph node dissection had no survival benefit in patients with EGJ carcinoma (8). In the current study, patients treated with spleen preservation had a significantly longer OS than those treated with splenectomy.…”
Section: Discussionmentioning
confidence: 43%
“…A recent randomised trial reported that splenectomy should be avoided because it increased operative morbidity without improving survival in patients undergoing total gastrectomy for proximal gastric cancer not invading the greater curvature (7). Moreover, a previous study reported that splenic hilar lymph node dissection could be omitted from EGJ carcinoma surgery without decreasing curability, based on the index of estimated benefit from lymph node dissection (8). However, this study did not establish the value of splenectomy or not in patients with EGJ carcinoma.…”
mentioning
confidence: 83%
“…However, the treatment of gastric cancer or EGJ cancer with splenectomy is controversial. Numerous studies on treatment of cancer with splenectomy have been published describing the high morbidity rates and low survival rate benefits of such treatment (25). However, Huang et al (26) reported that splenectomy is beneficial for splenic hilar lymph node dissections in patients with advanced proximal gastric cancer and is associated with improved survival rates.…”
Section: Rta (N=30) -------------------------------------------------mentioning
confidence: 99%